Data Sciences: From First-Order Logic to the Web - Serge Abiteboul (Collège de France, 2012)
Relational database management systems, using as foundations a formal language, first-order logic, serve as mediators between individuals and machines. With the increase in the volume of data disseminated on the Web, a "collective intelligence" is currently emerging, shaped by large search engines whose monopoly raises ethical and political questions. One of the main challenges for the coming years is the development of technologies that will make it possible to find, evaluate, validate, veri...